Management strategies for pasture recovery in guineagrass (Panicum maximum jacq.) and stargrass (Cynodon nlemfuensis vanderyst) pastures - Villalobos Villalobos, Luis Alonso (2018)
Presentación de investigación en American Forage & Grassland Council Annual Conference 2018